Introduction to immunology and immune disorders - Jean S. Marshall; Julia E. M. Upton; Harissios Vliagoftis; Kyla J. Hildebrand; Adam Byrne; Wade Watson (Allergy, Asthma & Clinical Immunology, 2024)
Abstract The body has a collection of physical barriers to prevent infection, but once these are overcome, we rely on our immune systems to protect us against a wide variety of infections. The complex mechanisms through which this is achieved are grouped into two lines of defense called the “innate” and “adaptive” immune systems. The innate immune system provides a rapid and tailored response to infection or injury often associated with inflammation. Innate immunity also promotes the development of acquired immunity. Specific, long-lasting responses against a particular infection are dependent on acquired immunity, and these provide immune memory, such that if we encounter the same pathogen again, we are better protected. Many diseases are related to defects in immune function which can lead to either a weakened or overactive immune response. Autoimmune diseases (where the immune system attacks tissues or organs) and allergies (where the immune system responds inappropriately to substances in our environment) are just two examples of conditions resulting from immune function defects. Improved understanding of immune processes provides tremendous opportunities for enhanced immunization strategies and immune-based therapies. This article provides an overview of the main components and functions of the immune system, and also serves as a primer to help readers understand the immunopathological disorders discussed in the remainder of this supplement.